Sexting can be sexy…if it's consensual: challenging victim blaming and heteronormativity in sext education - Natasha Richards (Janeway JS, 2021)
Young people's sexting is an area of concern amongst parents, policymakers, and educators.1 Much education around the topic of sexting focuses on risk and shame. My creative work, Sexting Scenes – what do you think?, is a film script intended as a sext education resource. It highlights the various reasons for and consequences of sexting, using an intersectional and sex-positive approach not rooted in risk or shame. I address issues of victim blaming and heteronormativity in sext education resources Tagged and Exposed. I utilise the theories of feminist scholars Amy Shields Dobson and Jessica Ringrose and applied theatre scholar Katherine Low. My previous placement at the School of Sexuality Education, my current PhD Practice-as-Research, and my experience as an applied theatre practitioner all informed the script content. The script incorporates multiple storylines, diverse characters, and reflective questions to challenge and question victim blaming and heteronormativity in relation to sexting. Keywords: sexting, sext education, victim blaming, heteronormativity, applied theatre